Maritain: la cuestión judía, la resistencia francesa y la Iglesia - Picón, María Laura (Sapientia, 2021)
The recent declassification of the Vatican documents of Pius XII’s pontificate are today’s object of analysis, debate, and study. This epistemological framework (macro history) will be vital to understand more about Jacques Maritain's performance as ambassador to the Holy See during the years 1945-1948 (micro history) and his apparent disagreement with some pronouncements of the Pontiff. In this article we will address some topics that will allow us to understand the philosopher's commitment to the French resistance, the Jewish cause and the Church, knowing that only in a few years we will be able to incorporate them into the macro history, thus being able to have a clearer view of the question.